Molecular Mechanisms and Current Pharmacotherapy of Peyronie’s Disease: A Review - Zhang, Fuxun; Qin, Feng; Yuan, Jiuhong (Frontiers in Pharmacology, 2021)
Peyronie’s disease (PD) is a localized fibrotic lesion of the penis that has adverse effects on men’s health. In this review, we summarized the molecular mechanisms and pharmacotherapies of PD. A literature search was conducted using PubMed and Cochrane Library during 2001–2020. Although no oral or topical medication demonstrated efficacy in monotherapy of PD, several intralesional medications have yielded promising results. Currently, the effective strategy in management of PD should be combined modality therapy, including but not limited to pharmacotherapy, mechanical therapy, and psychotherapy. Meanwhile, basic research is still necessary to facilitate the development of novel and more reliable treatments. In future, more attention should be given simultaneously to epigenetic changes, inflammatory cytokines, the abnormal wound-healing process, and profibrotic and anti-fibrotic factors to provide more options for this refractory disease.